Moral Message in The Fabel â€œAnt Struggleâ€ by Aleanzah as A Cultivation Of Peace-Loving Character Education in Junior High School Children - Erdiana, Adinda; Umaya, Nazla Maharani (Universitas PGRI Semarang, 2019)
The purpose of this paper is to describe the moral message contained in the label